1995
DOI: 10.1172/jci118083
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of generalized and regional adiposity to insulin sensitivity in men.

Abstract: The relative impacts of regional and generalized adiposity on insulin sensitivity have not been fully defined. Therefore, we investigated the relationship of insulin sensitivity (measured using hyperinsulinemic, euglycemic clamp technique with [3-3H] glucose turnover) to total body adiposity (determined by hydrodensitometry) and regional adiposity. The latter was assessed by determining subcutaneous abdominal, intraperitoneal, and retroperitoneal fat masses (using magnetic resonance imaging) and the sum of tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
413
5
16

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 682 publications
(469 citation statements)
references
References 67 publications
34
413
5
16
Order By: Relevance
“…Asian Indians have been shown to be more insulin-resistant than most other ethnic groups [27]. Preferential deposition and distribution of fat in the abdominal region is associated with reduced insulin-mediated glucose disposal, independent of an overall degree of obesity [28,29,30]. Anthropometric studies have shown that the distribution of fat differs between ethnic groups, and thus identical distributions of BMI in two populations could still reflect large differences with respect to the accumulation of intraabdominal fat, and Asian populations have been shown to be more prone to abdominal obesity and low muscle mass [27,31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Asian Indians have been shown to be more insulin-resistant than most other ethnic groups [27]. Preferential deposition and distribution of fat in the abdominal region is associated with reduced insulin-mediated glucose disposal, independent of an overall degree of obesity [28,29,30]. Anthropometric studies have shown that the distribution of fat differs between ethnic groups, and thus identical distributions of BMI in two populations could still reflect large differences with respect to the accumulation of intraabdominal fat, and Asian populations have been shown to be more prone to abdominal obesity and low muscle mass [27,31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intra-abdominal fat has been found to be a better determinant of insulin resistance than subcutaneous abdominal fat in most 1 but not all 2,3 studies. Subcutaneous abdominal fat may be divided into superficial and deep compartments that have different morphologies where only the deep compartment may produce insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal obesity is known to be an important factor in determining insulin resistance and an adverse lipid profile. [18][19][20] There is evidence that intraabdominal fat, in particular, is associated with insulin resistance. 21 The women in this study were mainly perimenopausal; only a small number had early menopause.…”
Section: Discussionmentioning
confidence: 99%